2007
DOI: 10.1128/aem.00166-07
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Handling as a Route of Exposure to Infectious Waterborne Cryptosporidium parvum Oocysts via Atlantic Blue Crabs ( Callinectes sapidus )

Abstract: Commercial Atlantic blue crabs (Callinectes sapidus) were exposed to 2.0 ؋ 10 4 infectious waterborne oocysts of Cryptosporidium parvum. The study demonstrated that blue crabs can transfer C. parvum oocysts to persons involved in handling or preparing crabs and that they may contaminate other surfaces or products during storage.Cryptosporidium parvum is a human enteric pathogen that can be transmitted very efficiently via the fecal-oral route (i.e., autoinfection and person-to-person) and indirectly via contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Their biology and ecology makes control of these parasites difficult. So, good hand washing in food preparation [4], controlleddissemination of cysts and oocysts in the farming environment via human waste management and good water management used to wash fresh products should prevent gastroenteritis in any group at risk and eliminate the spread of outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their biology and ecology makes control of these parasites difficult. So, good hand washing in food preparation [4], controlleddissemination of cysts and oocysts in the farming environment via human waste management and good water management used to wash fresh products should prevent gastroenteritis in any group at risk and eliminate the spread of outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Edible crabs may take up and retain human-virulent bacterial contaminants [13,14] and organic and inorganic pollutants from ambient water and sediments at levels posing risks to consumers [15]. And there is very little information on contamination of crabs with Cryptosporidium [4]. The authors demonstrated a mechanical passage of C. parvum oocysts via handling of fish caught in urban watersheds to the hands of recreational anglers.…”
Section: Cryptosporidium Parvum Found In Arthropods -Vectors Of Humanmentioning
confidence: 99%
See 3 more Smart Citations